Pelatihan Pembuatan Backdrop Kegiatan Kerohanian Islam Karang Taruna Garuda Muda Wonokromo Surabaya - Aryanto, Hendro; Abidin, M Rois (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2018)
Karang Taruna is one of the best teenager coaching alternatives. Through this organization, members of Karang Taruna obtain an environment that can develop creativity. Devotion to the community is one form of implementation of Tri Darma Higher Education, especially those who care about the social life of the community around the campus. The training followed by Karang Taruna Garuda Muda Pulo Wonokromo Surabaya will be expected to pass the knowledge and skills to others one of them training activities to make or design backdrop spirituality of Islam.Â